Usnic Acid and Usnea barbata (L.) F.H. Wigg. Dry Extracts Promote Apoptosis and DNA Damage in Human Blood Cells through Enhancing ROS Levels - Violeta Popovici; Elena Matei; Georgeta Camelia Cozaru; Mariana Aschie; Laura Bucur; Dan Rambu; Teodor Costache; Iulia Elena Cucolea; Gabriela Vochita; Daniela Gherghel; Aureliana Caraiane; Victoria Badea (MDPI AG, 2021)
Nowadays, numerous biomedical studies performed on natural compounds and plant extracts aim to obtain highly selective pharmacological activities without unwanted toxic effects. In the big world of medicinal plants, Usnea barbata (L) F.H. Wigg (U. barbata) and usnic acid (UA) are well-known for their therapeutical properties. One of the most studied properties is their cytotoxicity on various tumor cells. This work aims to evaluate their cytotoxic potential on normal blood cells. Three dry U. barbata extracts in various solvents: ethyl acetate (UBEA), acetone (UBA), and ethanol (UBE) were prepared. From UBEA we isolated usnic acid with high purity by semipreparative chromatography. Then, UA, UBA, and UBE dissolved in 1% dimethyl sulfoxide (DMSO) and diluted in four concentrations were tested for their toxicity on human blood cells. The blood samples were collected from a healthy non-smoker donor; the obtained blood cell cultures were treated with the tested samples. After 24 h, the cytotoxic effect was analyzed through the mechanisms that can cause cell death: early and late apoptosis, caspase 3/7 activity, nuclear apoptosis, autophagy, reactive oxygen species (ROS) level and DNA damage. Generally, the cytotoxic effect was directly proportional to the increase of concentrations, usnic acid inducing the most significant response. At high concentrations, usnic acid and U. barbata extracts induced apoptosis and DNA damage in human blood cells, increasing ROS levels. Our study reveals the importance of prior natural products toxicity evaluation on normal cells to anticipate their limits and benefits as potential anticancer drugs.